Nexus between organizational citizenship behavior and psychological wellbeing: emotional intelligence as a pathway - Prasad, KDV; Singh, Shivoham; Srinivas, Ved; Vaidya, Rajesh; Dave, Krishna Kant (Frontiers in Psychology, 2024)
Aim/purpose -The aim of this study is to investigate the nexus between organizational citizenship behavior and psychological well-being and assess the moderating and mediating effects of emotional intelligence (EI) on the relationship between psychological well-being of IT-enabled Sector employees in Hyderabad. Design/methodology/approach -To measure the study variables of organizational citizenship behavior (OCB) and emotional intelligence (EI) on psychological well-being (PWB) data were gathered using a questionnaire. The mediating and moderating effects of emotional intelligence on the relationship between organizational citizenship behavior and psychological well-being was also assessed. The was reliable as indicated by the Cronbach's alpha coefficient statistic that between 0.79 to 0.91. Findings -Three hundred valid responses were considered for SEM analysis using AMOS, version 28. . The SEM analysis revealed that the impact of exogenous variables OCB and EI were statistically significant (p<0.001) on endogenous variable psychological well-being of IT-enabled industry employees. Furthermore, EI partially mediates psychological well-being through the OCB of information technology employees. This empirical study also examined the moderating effects of EI on the psychological well-being of information technology-enabled employees through OCB. The slope analysis reveals that emotional intelligence strengthens the positive association between OCB and the PWB of IT-enabled sector employees. EI and OCB enhance PWB and employee performance.Research implications/limitations -The findings of this study have several important implications for organizations in the IT sector and can be used to develop strategies for promoting OCB and EI among employees. The structural relationships between PWB and OCB in the context of hotel employees and reported positive effects of OCB on hotel employees are well documented. The limitations are the data were collected from the Information Technology employees of Hyderabad Metro. There are some subjectivity and cultural issues which were elaborated at the end Contribution/Originality: This empirical study helps to clarify the relationship between organizational citizenship behavior, psychological well-being, and the mediator and moderator variable emotional intelligence. The study also comprehends the available literature and adds value to the existing theoretical knowledge and behavioral studies.